Nothern Survey Equipment & Company / Zambri Hassan ... [et al.]. - Hasan, Zambri; Khamis, Mohamad Zaidi; Adnan, Shahrul Amri; Abd Mutalib, Mohd Asrizal; Said, Mohd Ridzuan (2002)
Nowadays the growth and the development of the business arise in Alor Setar is very well encouraged for setting business growth oriented by the management efficient and customer satisfaction. Northen Survey Equipment Company based on equipments supplier for constructions, licensed surveyors, Department of Survey and Mapping, Jabatan Kerja Raya, Pejabat Tanah dan Galian, Jabatan Pengairan dan Saliran and high learning educations likes universities and olytechnics. Our business hour between 9.00 a.m until 5.15 p.m. Northen Survey Equipment Company is established to upgrade the local entrepreneur in business scale. For the first step Northen Survey Equipment Company established in Alor Setar with 11 workers. This company will concentrate to provide the fast and good services. We hope to open the branch in the whole Peninsular of Malaysia on 3 years ahead.